Le sanctuaire suburbain d’Augustodunum de la Genetoye à Autun (Saône-et-Loire) : apport de l’approche combinée de données spatialisées à la restitution du théâtre antique du Haut du Verger - Gilles Bossuet; Antoine Louis; Filipe Ferreira; Yannick Labaune; Clément Laplaige (Gallia)
The first investigations undertaken on the site of the antique theatre Haut du Verger at Autun (Saône-et-Loire), in 2013, were followed by an unusual joint effort between an architecture specialist, geophysicians and archaeologists. The analyses of the aerial photography, the geophysical prospecting and the excavation campaign data enabled them to reproduce the building’s plan as a final synthesis of the planimetric and architectural data. This synthesis also shows some geometrical features about the building’s outline that could reveal several stages of restructuration of the building. This reconstruction of the building’s plan aims to optimize the architectural development of the investigation. It seems to highlight an unusual building principle in the theatre and mostly proves the relevance of this multidisciplinary joint effort.